KONSEP FUNGSI PENDEGELASIAN KEPEMIMPINAN DALAM PERSPEKTIF AL-QUR’AN - Ardian (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2025)
Delegation is a crucial leadership function that determines the effectiveness and sustainability of an organization, including in Islamic Educational Management. This article aims to examine the concept and function of leadership delegation from a Qur'anic perspective. This research uses a qualitative approach with library research, drawing on the Qur'an, hadith, and scientific literature related to Islamic leadership and management. The results of the study indicate that delegation, from a Qur'anic perspective, is not merely a managerial technique but a mandate with moral and spiritual dimensions. The functions of leadership delegation include increasing work effectiveness and efficiency, developing human resource competencies, establishing responsibility and accountability, enhancing motivation and trust, and ensuring leadership continuity through cadre development. Thus, Qur'anic leadership delegation serves as an important foundation for managing Islamic educational institutions that are oriented toward spiritual values, performance, and accountability.